2020
DOI: 10.21203/rs.3.rs-112257/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanical energy-induced CO2 conversion using liquid metals

Abstract: We report a green carbon capture and conversion technology offering scalability and economic viability for mitigating CO2 emissions. The technology uses suspensions of gallium liquid metal to reduce CO2 into carbonaceous solid products and O2 at near room temperature. The nonpolar nature of the liquid gallium interface allows the solid products to instantaneously exfoliate, hence keeping active sites accessible. The solid co-contributor of silver-gallium rods ensures a cyclic sustainable process. The overall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…8 In another example, a mechanicallyinduced catalytic process using a suspension of Ga nanodroplets and Ag/Ga intermetallic nanorods were utilized for the reduction of CO 2 into solid carbonaceous products and O 2 at room temperature. 217 GaPt nanoparticles created by galvanic replacement have also been used for the oxidation of methanol and Fig. 7 (a) Room temperature catalytic process of CO 2 reduction to solid carbon on LM/Ce electrodes.…”
Section: Catalysismentioning
confidence: 99%
“…8 In another example, a mechanicallyinduced catalytic process using a suspension of Ga nanodroplets and Ag/Ga intermetallic nanorods were utilized for the reduction of CO 2 into solid carbonaceous products and O 2 at room temperature. 217 GaPt nanoparticles created by galvanic replacement have also been used for the oxidation of methanol and Fig. 7 (a) Room temperature catalytic process of CO 2 reduction to solid carbon on LM/Ce electrodes.…”
Section: Catalysismentioning
confidence: 99%
“…41 However, the performance of these composites can deteriorate if carbonaceous materials adhere to the catalytic metal surface. Theoretically, this issue can be resolved by replacing the metal component with a liquid metal, which is based on the phenomenon of LME, as proved experimentally by J. Tang et al 42 The liquid gallium interface allows the carbonaceous products to be spontaneously exfoliated and removed from the surface of mica through mechanical agitation during the catalyst reaction, maintaining the accessibility of the active sites. During the CO 2 reduction process, Ga (0)s converted into Ga(1), while CO 2 is activated into the CO 2 ˙ − radical.…”
Section: Resultsmentioning
confidence: 99%
“…After that, they also studied more complex motions to manipulate the motion of liquid metal. But there is still a long way to go to realize a practical liquid metal robot. 3)Liquid metal catalyzes energy reactions: recent studies have reported that the use of mechanical energy‐induced methods to convert CO 2 to carbon in Ga liquid metal suspensions near room temperature, [ 361 ] and the low melting point of EGaIn can be used to convert CO 2 to carbon at room temperature without supplementary reductant, [ 362 ] which shows that EGaIn has a great potential for energy recovery and utilization. Moreover, it is also expected to reduce the greenhouse effect and play an important role in environmental protection.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%